Is sustainability certification for biochar the answer to environmental risks? - Cowei, Annete L.; Downie, Adriana E.; George, Brendan H.; Singh, Bhupinder‑Pal; Van Zwieten, Lukas; O’Connell, Deborah (Pesquisa Agropecuaria Brasileira, 2012)
Biochar has the potential to make a major contribution to the mitigation of climate change, and enhancement of plant production. However, in order for biochar to fulfill this promise, the industry and regulating bodies must take steps to manage potential environmental threats and address negative perceptions. The potential threats to the sustainability of biochar systems, at each stage of the biochar life cycle, were reviewed. We propose that a sustainability framework for biochar could be adapted from existing frameworks developed for bioenergy. Sustainable land use policies, combined with effective regulation of biochar production facilities and incentives for efficient utilization of energy, and improved knowledge of biochar impacts on ecosystem health and productivity could provide a strong framework for the development of a robust sustainable biochar industry. Sustainability certification could be introduced to provide confidence to consumers that sustainable practices have been employed along the production chain, particularly where biochar is traded internationally.